2005
DOI: 10.1007/s10067-005-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Q angle and joint hypermobility and Q angle values in different positions

Abstract: Patellar malalignment is the most important reason for anterior knee pain. Patellar alignment is commonly determined by the measurement of the quadriceps (Q) angle. In this study, our primary aim was to investigate the Q angle difference between healthy individuals with and without joint hypermobility. The other objectives were to compare the Q angle values, which were measured in supine and upright positions, to determine hypermobility frequency among healthy males in a certain population, and to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
3
24
0
2
Order By: Relevance
“…12 The study further found same result on paired sample t-test in their three subgroups having variable joint hypermobility. 12 However, we have not studied the effect of joint hypermobility on Q angles.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…12 The study further found same result on paired sample t-test in their three subgroups having variable joint hypermobility. 12 However, we have not studied the effect of joint hypermobility on Q angles.…”
supporting
confidence: 70%
“…12 The study further found same result on paired sample t-test in their three subgroups having variable joint hypermobility. 12 However, we have not studied the effect of joint hypermobility on Q angles. Study on effect of position of limb and Q angle revealed no significant relation between them, however, isometric quadriceps contraction showed significant effects on Q angle for both men and women (p < 0.001).…”
supporting
confidence: 70%
“…The Q angle has come to be accepted as an important factor in assessing knee joint function [10]. An increase in the Q angle beyond the normal range is considered indicative of extensor mechanism misalignment, and has been associated with was Patellofemoral pain syndrome, knee joint hyper mobility, and patellar instability [11,12]. It has also been suggested that an abnormal Q-angle may also influence neuromuscular response and quadriceps reflex response time, an Aetiological factor in patella femoral pain syndrome [13].…”
Section: Introductionmentioning
confidence: 99%
“…Knees with increased H angle suffer increase of the lateral patellofemoral contact pressure during the flexion movement, and those with decrease of this angle suffer increase of the medial patellofemoral contact pressure in the same movement. Alterations in this angle may determine compression and sprains in the capsuloligamentar structures, lead to knee instability and development of arthrosis 26,27 . There is divergence concerning about the reference value for the H angle, and Magee 3 and Cabral and Monteiro…”
Section: Discussionmentioning
confidence: 99%
“…According to Tribastone 29 , the normal angle should be of 14th to 20th, regardless of gender. According to Sendur et al and Mizuno et al 26,27 , the values of this angle range between 6 and 27th, with mean value of 15th, regardless of gender. Despite this important variation in the literature, the results of the present study revealed means which are according to the authors (16.8 and 18.9°).…”
mentioning
confidence: 94%